Terapia cognitivo - conductual e intentos de suicidio. - Castro Aldás, Viviana Zarai (2025)
At present, suicide attempts and other suicidal behaviors that precede it have been a latent and worrisome problem for mental health professionals; for this reason, several researchers have searched for psychotherapeutic strategies to reduce the impact of this symptomatic condition and thus decrease the number of completed suicides. The objective of this research is to analyze the cognitive behavioral therapy applied in the treatment of people with suicide attempts. The research was bibliographic and responded to the descriptive level, gathering information from different Internet sources such as online books, web pages, and scientific articles. Specifically, the specific selection criteria extracted these from the Scielo, Pubmed, Web of Science, and Scopus repositories. The final sample consisted of 20 scientific articles which were subjected to a methodological quality qualification process using the Critical Review Form - Quantitative Studies (CRF-QS). The findings suggest that the techniques used to address and reduce suicidal attempts and suicidal ideation are cognitive restructuring, psychoeducation, emotional regulation, and problem-solving, methods that belong to the cognitive-behavioral intervention, therapy that has shown high effectiveness by presenting favorable results showing a significant reduction of selfharm attempts and suicidal ideation, in addition to the reduction of symptoms that can lead individuals to perform suicidal acts. It is also a procedure that has surpassed other therapeutic approaches due to the positive results that have been evidenced and the techniques used oriented to each aspect of suicidal ideation.